PENERAPAN MODEL PEMBELAJARAN THINK PAIR SQUARE (TPS) DENGAN MENGGUNAKAN LKS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DI KELAS X SMA NEGERI 2 PEMATANGSIANTAR - Winmery Lasma Habeahan (MES: Journal of Mathematics Education and Science, 2019)
Abstract. The purpose of this study was to determine whether using the TPS learning model by using LKS can improve student learning outcomes in the material system linear equation two variable in class X Senior High Public School 2 of Pematangsiantar. The type of research used is classroom action research with 2 cycles. Subjects of class X-IPA 7. On the implementation of the first cycle of action, the result of the analysis of tests of students at the moderate (≥ 65) category in a classical manner were still not achived because only 52.78% of students were completed, with a grade average 65.00. After the implementation of the second cycle of action, the learning outcomes of students in the medium minimum category (≥ 65) have been achived classically, namely 86.11% with an average value 73.75. The increase in students’ mathematics learning outcomes from cycle I to cycle II was 21.11%. Based on the result of the above research it can be concluded that the application of the TPS learning model using LKS can improve student learning outcomes.Keywords: Laerning Outcomes, Think Pair Square (TPS), LKS